Optimizing the First 1000 Days of Life Through Stunting Prevention Education - Imella Annisah; Yasinta Dewi Kristianti; Dwi Wahyuningsih; Rosa Susanti (ADI Pengabdian Kepada Masyarakat, 2026)
Stunting is one of the most critical nutritional problems in Indonesia, significantly affecting children's physical and cognitive development. According to national data, the prevalence of stunting in rural areas remains relatively high. In Kasomalang Kulon Tourism Village, Subang Regency, West Java, the issue is exacerbated by the limited capacity of posyandu cadres in conducting anthropometric measurements, low community nutrition literacy, and the underutilization of abundant local food resources. These challenges hinder optimal stunting prevention efforts, especially during the first 1000 days of life (HPK), a crucial window for child development. This community service program aims to optimize the role of posyandu cadres in preventing stunting through targeted education and empowerment on the first 1000 days of life (HPK) in Kasomalang Kulon Tourism Village. The program applied a community empowerment approach using the Participatory Rural Appraisal (PRA) method combined with the Triple-A framework (Assessment, Analysis, and Action). The activities consisted of social mapping, participatory workshops, intensive training on anthropometric measurements (weight, height, and head circumference), nutrition education, demonstrations of local food-based complementary feeding (MP-ASI), and regular monitoring and evaluation using pre-test and post-test questionnaires. The program involved 25 posyandu cadres and community members over a three-month period. The results demonstrated significant improvements in cadres knowledge (from 62% to 89%), skills in anthropometric measurements, and confidence in delivering nutrition counseling. In addition, the program successfully increased awareness and utilization of local food resources for nutritious MP-ASI. The participatory approach also strengthened community engagement and ownership in stunting prevention initiatives. This study concludes that community-based empowerment interventions using participatory methods are highly effective in enhancing the capacity of posyandu cadres and supporting sustainable stunting prevention efforts. Strengthening cadre roles through education on the first 1000 days of life can serve as a strategic model for similar programs in other rural areas.